Calibrated ages of Struban Bog (STR) peat core from the Outer Hebrides in Scotland - Lisa C Orme (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.